2015
DOI: 10.1890/es15-00223.1
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of leaf phenology to changing temperature among plant species and geographical regions

Abstract: Shifts in plants' phenophases caused by climate change can strongly affect the ecosystem structure and function. Temperature sensitivity, which is expressed as the date of phenological event change for per degree Celsius change of temperature (days °C−1), has been widely used to characterize the plants' responses to changed temperature. In this study, we analyzed the temperature sensitivity of leaf phenology (leaf unfolding date, LUD; leaf falling date, LFD) for more than 700 plant species based on the phenolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Accordingly, some degree of seasonality is often recorded for vegetative and reproductive phenophases in tropical forests at the community level, and the regulation of seasonality has been linked to oscillations in air temperature, photoperiod and precipitation [22,25,26] However, assessments of the phenodynamics based on community-structure parameters and its regulation by combined effects of proximate factors are still unresolved matters for tropical forests. As such, ground-based phenological data at the forest community level are important for statistical models of vegetation dynamics, by means of quantification of relationships with environmental descriptors (e.g., [26][27][28]). …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, some degree of seasonality is often recorded for vegetative and reproductive phenophases in tropical forests at the community level, and the regulation of seasonality has been linked to oscillations in air temperature, photoperiod and precipitation [22,25,26] However, assessments of the phenodynamics based on community-structure parameters and its regulation by combined effects of proximate factors are still unresolved matters for tropical forests. As such, ground-based phenological data at the forest community level are important for statistical models of vegetation dynamics, by means of quantification of relationships with environmental descriptors (e.g., [26][27][28]). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to observations showing earlier spring plant phenology with global warming, numerous studies have also reported no response or even delays of spring phenophases (Bradley, Leopold, Ross, & Huffaker, 1999;Dorji et al, 2013;Sherry et al, 2007;Zhang, Tarpley, & Sullivan, 2007;Zhang et al, 2015Zhang et al, , 2016, and the concept of winter chilling has increasingly been used to explain these seemingly inconsistent plant phenological responses to increasing temperature (Basler & K€ orner, 2014;Cook, Wolkovich, & Parmesan, 2012;Primack et al, 2009). Several studies have reported that the requirements of winter chilling have to be fulfilled before a plant is able to respond to forcing temperatures for leaf unfolding (temperatures higher than the base temperature (e.g., 5°C) for thermal accumulation; Chuine, Cour, & Rousseau, 1998Kramer, 1994;Sarvas, 1974).…”
mentioning
confidence: 69%
“…R eaumur's theory has been supported by many studies and has also been invoked to explain the earlier spring phenology with rising global temperature (Fitter & Fitter, 2002;Fu, Piao, et al, 2015;Menzel et al, 2006;Primack et al, 2009;Shen, Cong, & Cao, 2015;Shen et al, 2014;Zhang, Yuan, Liu, & Dong, 2016;Zhang, Yuan, Liu, Dong, & Fu, 2015). R eaumur's theory has been supported by many studies and has also been invoked to explain the earlier spring phenology with rising global temperature (Fitter & Fitter, 2002;Fu, Piao, et al, 2015;Menzel et al, 2006;Primack et al, 2009;Shen, Cong, & Cao, 2015;Shen et al, 2014;Zhang, Yuan, Liu, & Dong, 2016;Zhang, Yuan, Liu, Dong, & Fu, 2015).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, it should be noted that the temperature threshold (TcritTm) of grassland was lower than that of woody species in the same latitudinal zone. This phenomenon might be related to the local climate and plant species[57]. …”
Section: Discussionmentioning
confidence: 99%